Meteorological Data at Mizuho Camp, Antarctica in 1971-1973 - ヤマダ, トモミ; ササキ, ヒロシ; カワグチ, サダオ; YAMADA, Tomomi; SASAKI, Hiroshi; KAWAGUCHI, Sadao (National Institute of Polar Research, 1974)
P(論文) departmental bulletin paper